2020
DOI: 10.1111/odi.13573
|View full text |Cite
|
Sign up to set email alerts
|

Screening for prevalence and abundance of Capnocytophaga spp by analyzing NGS data: A scoping review

Abstract: Background. Capnocytophaga spp. are commensal bacteria of the oral cavity and constitute a genus of the core microbiome.Objective. This genus is responsible for many local and systemic conditions in both the immunocompetent and immunocompromised, but its beneficial or deleterious role in the microbiota has been little explored.Design. Online databases were used to identify papers published from 1999 to 2019 based on next-generation sequencing (NGS) data to study comparative trials. Work using other identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…In this study, we describe a novel species belonging to the genus Capnocytophaga isolated from a dental plaque sample of a male with gingivitis living in Marseille, France. The other Capnocytophaga species currently described are also generally isolated from the human oral cavity ( C. gingivalis , C. granulosa , C. haemolytica , C. leadbetteri , C. ochracea , and C. sputigena ), and also that of dogs and cats ( C. canimorsus , C. cynodegmi , and C. canis ) [ 33 ]. Among members of the genus Capnocytophaga , the Marseille-Q4570 T strain shared the highest 16S rRNA gene sequence similarities (97.24% sequence identity) with C. leadbetteri strain AHN8855 T , an anaerobic Gram-negative rod bacterium isolated from the oral cavity of children [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we describe a novel species belonging to the genus Capnocytophaga isolated from a dental plaque sample of a male with gingivitis living in Marseille, France. The other Capnocytophaga species currently described are also generally isolated from the human oral cavity ( C. gingivalis , C. granulosa , C. haemolytica , C. leadbetteri , C. ochracea , and C. sputigena ), and also that of dogs and cats ( C. canimorsus , C. cynodegmi , and C. canis ) [ 33 ]. Among members of the genus Capnocytophaga , the Marseille-Q4570 T strain shared the highest 16S rRNA gene sequence similarities (97.24% sequence identity) with C. leadbetteri strain AHN8855 T , an anaerobic Gram-negative rod bacterium isolated from the oral cavity of children [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, Citrobacter rodentium has been shown to increase the proliferation of colon cancer and to activate cancer promoting biochemical pathways ( Umar, 2012 ), and Haemophilus influenzae has been shown to increase the proliferation of k-ras positive lung adenocarcinoma ( Jungnickel et al., 2017 ). There were no studies of Parvimonas or Capnocytophaga roles in cancer, although their prevalence has been reported to be increased in several different tumour microenvironments ( Jolivet-Gougeon and Bonnaure-Mallet, 2021 ; Kabwe et al., 2021a). No research detailing the role of Selenomonas or Rothia in cancer progression has been reported either.…”
Section: Discussionmentioning
confidence: 99%
“…The most transparent study designs to synthesize biological/laboratory data are “systematic” (Page et al, 2021) and “scoping” reviews (Tricco et al, 2018; Page et al, 2021). While SRs have been more commonly used in recent years (Pérez‐Chaparro et al, 2014; 2019; Dereka et al, 2022), scoping reviews are newer in the healthcare field (Belmok et al, 2020; 2021). Choosing between these two study designs may be challenging due to the novelty of the topic and the fact they both involve a peer‐reviewed search strategy, summarization, and appraisal of data collected.…”
Section: Scoping Review Systematic Reviewmentioning
confidence: 99%
“…If a single, specific, objective, and focused question is identified, a systematic review would be the best choice (Arias‐Bujanda et al, 2020). On the other hand, if authors are addressing more heterogeneous questions, or attempting to map, identify and discuss broader concepts, a scoping review would be better suited (Belmok et al, 2020; Jolivet‐Gougeon & Bonnaure‐Mallet, 2021; Schmidlin et al, 2021). SRs tend to yield more solid evidence, as, contrary to scoping reviews, they demand the use of methodological quality assessment tools.…”
Section: Scoping Review Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation